PENGARUH VIRGIN COCONUT OIL TERHADAP RUAM POPOK BAYI USIA 0 – 24 BULAN DI PMB RIRIN DS TAHUN 2023 - Simanjuntak, Farida Mentalina; Junita, Friska; Siregar, Renince Siregar (STIKes Medistra Indonesia, 2026)
Background: Diaper rash is the most common skin inflammation suffered by babies caused by bacteria and viruses around the genitals, anus, buttocks, thigh folds, and lower abdomen. The incidence rate of diaper rash in 2018 around the world according to the World Health Organization (WHO) skin irritation (diaper rash) is quite high, which is 25% out of 1,000,000 in Indonesia, the incidence rate of diaper rash found in Indonesia has reached 7-35% of 4,746,438 babies. Objective: To determine the effect of VCO administration on the incidence of diaper rash at the age of 0 - 24 months.l. Methods: Types of quantitative research as well as observational analytics and with Quasi Experimental design. The data analysis carried out was by univariate and bivariate analysis. The sample of this study is 20 people. Results: Of the 20 respondents who had diaper rash before VCO, there were 6 (30%) respondents with Diaper Rash degree 1, there were 10 (50%) respondents with Diaper Rash degree 2, and there were 4 (20%) respondents with Diaper Rash degree 3. After the VCO was given, there were 12 (60%) respondents who did not have diaper rash, there were 6 (30%) respondents with 1st degree diaper rash, and there were 2 (10%) respondents with 2nd degree diaper rash. Conclusion: The results of the wilcoxon test showed p value = 0.000< 0.05, it was concluded that Ho was rejected and Ha was accepted which means that the administration of VCO in babies with diaper rash had an effect before and after